2019
DOI: 10.3892/mmr.2019.10369
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of metformin on cell proliferation, apoptosis, migration and invasion in A172 glioma cells and its mechanisms

Abstract: The purpose of the present study was to determine the effects of metformin on the inhibition of proliferation, apoptosis, invasion and migration of A172 human glioma cells in vitro and determine the underlying mechanism. The effects of metformin at different concentrations (0, 0.1, 1 and 10 mmol/l) on the inhibition of A172 cell proliferation were detected using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Cell apoptosis was detected by flow cytometry. Caspase-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Research conducted by Xiong et al, focused on observing the effect of metformin on AMPK activity in gliomas. They have shown that metformin causes an increase in AMPK expression and a decrease in mTOR protein expression, thereby inhibiting proliferation and increasing tumor cell apoptosis [85]. This seems to confirm the role of AMPK/mTOR signaling pathway in the mechanism of the action of metformin, indicating its potential use in anti-cancer therapy.…”
Section: Metformin and Adenosine Monophosphate-activated Protein Kinamentioning
confidence: 66%
See 4 more Smart Citations
“…Research conducted by Xiong et al, focused on observing the effect of metformin on AMPK activity in gliomas. They have shown that metformin causes an increase in AMPK expression and a decrease in mTOR protein expression, thereby inhibiting proliferation and increasing tumor cell apoptosis [85]. This seems to confirm the role of AMPK/mTOR signaling pathway in the mechanism of the action of metformin, indicating its potential use in anti-cancer therapy.…”
Section: Metformin and Adenosine Monophosphate-activated Protein Kinamentioning
confidence: 66%
“…A recent work presented by Xiong et al, has confirmed that metformin can also have an effect on this mechanism. In their work, the authors proved that it could affect the increase in caspase 3 activity in human GBM cells [85]. This suggests the possibility of using the mechanism of metformin-induced apoptosis in cancer therapy.…”
Section: Participation In the Caspase 3 Bax And Bcl2 Regulationmentioning
confidence: 90%
See 3 more Smart Citations